Dual role of Cathepsin S in cutaneous melanoma: insights from mendelian randomization and bioinformatics analysis - Linsa Zhou; Qiang Zhou; Qian Guo; Peng Lai; Chen Rui; Wanqing Li; Xuemei Chen; Yue Zhuo; Xiaoping Zhong; Sen Lin (BMC Cancer)
Abstract Background Cutaneous melanoma (CM) is strongly associated with ultraviolet (UV) radiation, which contributes to the transformation of melanocytes into melanoma by inducing specific DNA damage. Here, we investigated the causal relationship between CM and genes related to sun-damaged skin, exploring specific target genes through various bioinformatics analyses. Methods The Gene Expression Omnibus (GEO) database was used to obtain differential genes for CM and normal skin, and the Genome-Wide Association Studies (GWAS) analysis offered summary-level melanoma data for CM. Mendelian randomization (MR) analyses were used to examine the correlated linkage between CM and sun-exposed skin genes. The MR studies were conducted mainly using Inverse Variance Weighting (IVW), MR-Egger, Weighted Median, simple and weighted patterns to predict the correlation between sun-exposed skin and CM. Finally, the role of target genes in CM was revealed by pan-cancer analysis, expression and immune-infiltration evaluations, immuno-checking targeting analysis, immunotherapy response analysis, survival analysis, and protein-protein interactions (PPI) network and enrichment analyses. Result Using matrix data from the GSE15605, GSE46517, and GSE111452 datasets, bioinformatics analysis revealed 232 differentially expressed genes (DEGs) between CM and typical tissues. MR analysis indicated that only CTSS has a deleterious effect linking skin exposure to sunlight and CM. Analysis of CTSS expression in tumors and tissues, along with the construction of a prognostic model, revealed that CTSS expression was higher in both primary CM and metastatic CM compared to normal skin tissue. However, patients with higher CTSS expression had a higher prognosis. In addition, high CTSS expression was significantly and positively correlated with tumor mutation rate, tumor microenvironment, immune cell infiltration, immune checkpoints and immunotherapy efficacy. Conclusion Using MR analysis, we found a positive causal relationship between the CTSS gene in sun-exposed skin and CM. Additionally, increased CTSS may provide a basis for biomarker prediction of CM prognosis, immune status and immunotherapy.